Intervju z dr. Francem Pedičkom o "minulem delu" - Pediček, Franc (Šolsko polje, 2006)
At the beginning of the interview Dr. Pediček speaks about teachers, educationand pedagogical theory. He also speaks about his personal experience from the second consultation of Slovenian educationalists in Bled, which was akind of turning point in his pedagogical theoretical work. He then mentions his numerous publications and speaks about being director of the Educational Research Institute. Three major issues that stand out in the work of the interviewee are highlighted: educational advisory work, pedagogical theory with an anthropological orientation and the theory of terminology in science with emphasis on teacher training. These issues are then presented in detail. At the end of the interview, by way of concluding Pediček's work in pedagogical theory, there is also mention of the study Patterns of Slovenian Pedagogy: a presentation of ideological contradictions and issues dealt with in Slovenian pedagogy 1945-1988, which provoked his second political and conceptual dispute, although this was not as politically dangerous as that in Bled.
Keywords: Pediček, Franc, 1922-; biografije; pedagogika; pedagogy; intervjuji